2008
DOI: 10.1586/17469899.3.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous bioactive lipids and the regulation of conventional outflow facility

Abstract: SummaryPerturbation of paracrine signaling within the human conventional outflow pathway influences tissue homeostasis and outflow function. For example, exogenous introduction of the bioactive lipids, sphingosine-1-phosphate, anandamide or prostaglandin F 2α , to conventional outflow tissues alters the rate of drainage of aqueous humor through the trabecular meshwork, and into Schlemm's canal. This review summarizes recent data that characterizes endogenous bioactive lipids, their receptors and associated sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 102 publications
1
15
0
Order By: Relevance
“…110 Currently, however, only little is known about the role played by PLA2s in AH outflow and IOP despite the known critical and predominant role of this class of enzymes in producing the eicosanoids and lysophospholipids that are confirmed to modulate AH outflow and IOP. 111 Very recently, we not only confirmed the distribution pattern of 2 isoforms of calcium-independent phospholipaseA2 (iPLA2b and iPLA2g) in human TM and cultured TM cells, but also established their role in regulation of AH outflow facility. 81 Using isoform-specific small molecular inhibitors of iPLA2 (S-Bromoenol lactone) and (R-Bromoenol lactone), it has been demonstrated that iPLA2g plays a significant role in the regulation of TM cell contractile properties, cell shape, and cell adhesive interactions by controlling MLC phosphorylation.…”
Section: Raosupporting
confidence: 63%
“…110 Currently, however, only little is known about the role played by PLA2s in AH outflow and IOP despite the known critical and predominant role of this class of enzymes in producing the eicosanoids and lysophospholipids that are confirmed to modulate AH outflow and IOP. 111 Very recently, we not only confirmed the distribution pattern of 2 isoforms of calcium-independent phospholipaseA2 (iPLA2b and iPLA2g) in human TM and cultured TM cells, but also established their role in regulation of AH outflow facility. 81 Using isoform-specific small molecular inhibitors of iPLA2 (S-Bromoenol lactone) and (R-Bromoenol lactone), it has been demonstrated that iPLA2g plays a significant role in the regulation of TM cell contractile properties, cell shape, and cell adhesive interactions by controlling MLC phosphorylation.…”
Section: Raosupporting
confidence: 63%
“…They have also been proposed to be potential endogenous bioactive lipids in the regulation of conventional outflow facility. 6 Sphingolipids are also known as regulators of cell proliferation, differentiation, autophagy, cellular interactions, migration, signaling, and cell death. 28 Mammalian sphingolipids are Error in Da has been provided from theoretical data.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids have been found to regulate aqueous humor outflow in the eye. 6,7 Currently, the most used, but not always effective drugs approved to control outflow, are prostaglandin F 2a lipid analogs, discovered originally in 1955 from the iris, 8 they reduce IOP by directing aqueous humor drainage primarily through the uveoscleral outflow pathway. 9 Conceivably, the TM undergoes changes during aging and potentially under elevated IOP, which has not been fully understood.…”
mentioning
confidence: 99%
“…1 The trabecular outflow pathway drains 60% to 90% of the AH under physiologic conditions while the remainder of AH exits via the uveoscleral drainage pathway, with its relative contribution increasing in conditions of sustained IOP elevation. 1,2 Prostaglandin F2alpha (PGF2a) analogues are the most widely prescribed IOP-lowering drugs, mainly acting by increasing uveoscleral outflow. 3 They include latanoprost, travoprost, tafluprost, and bimatoprost, with the latter being the least potent in vivo but among the most effective of the PGF2a analogues.…”
Section: Methodsmentioning
confidence: 99%